Fabrication and elastic analysis of woven abaca fabric reinforced unsaturated polyester composite - Polinga, Lady Mariannne E. (2009)
The abaca fiber, also known as Manila hemp, that is endemic in the Philippines, was previously shown to have mechanical properties suitable for composite application, where it served as a unidirectional filler or reinforcing material to unsaturated polyester. Considering that in composite preparation, reinforcements in the form of woven fabrics offer a lot of convenience in terms of handling and composite fabrication, it will be beneficial to understand the performance of woven abaca fabric as a reinforcing material to unsaturated polyester. In this study, various configurations of the abaca fiber, i.e. unidirectional or woven, were explored and the mechanical properties of the resulting composites were determined and related to various fabric and composite constructions parameters. All composites were fabricated via vacuum bagging method and experimentations were divided into two phases; Phase 1 delved on the variation of the mechanical properties of lamina composites with fiber preparation sequence and weaving construction; and Phase 2 delved on mechanical properties of multi-layered composites as a function of inter-lamina distance, lamina configuration and number of lamina layers. Results of phase 1 showed that composite reinforced with fabric constructed using 20 reed with two ends per dent which underwent chemical treatment after weaving exhibited the highest tensile strength at 65.155 MPa. Such configuration struck the needed balance between the fiber count and the gap between adjacent yarns, which are the physical manifestations of varying fabric construction in the composite. Furthermore, it was shown that, in a 2 layered composite, higher Young's modulus was exhibited by samples with low inter-lamina distance and with shifting of fabric layers. The elastic modulus achieved by the composite with this structural configuration is 2.07 GPa. However, in the 4 layered composites, crack formation was observed and is believed to be related to the shrinkage and warpage as suggested by other literatures. Investigation of other weaving patterns, fiber sizing and modification of the matrix system are recommended.
"November 2009."
Thesis (M.S. Materials Science and Engineering)--University of the Philippines, Diliman.
Keywords: Abaca (Fiber) -- Properties -- Testing; Abaca (Fiber) -- Philippines; Polyester fibers